2014
DOI: 10.1128/aem.02820-14
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Vibrio cholerae, V. vulnificus, and V. parahaemolyticus in Oysters (Crassostrea virginica) and Clams (Mercenaria mercenaria) from Long Island Sound

Abstract: Vibriosis is a leading cause of seafood-associated morbidity and mortality in the United States. Typically associated with consumption of raw or undercooked oysters, vibriosis associated with clam consumption is increasingly being reported. However, little is known about the prevalence of Vibrio spp. in clams. The objective of this study was to compare the levels of Vibrio cholerae, Vibrio vulnificus, and Vibrio parahaemolyticus in oysters and clams harvested concurrently from Long Island Sound (LIS). Most pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…than did oysters. A study by Jones et al (23) that was conducted in Long Island Sound also found that the levels of these human pathogens, as well as Vibrio cholerae, were lower in clams than in oysters.…”
Section: Discussionmentioning
confidence: 99%
“…than did oysters. A study by Jones et al (23) that was conducted in Long Island Sound also found that the levels of these human pathogens, as well as Vibrio cholerae, were lower in clams than in oysters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted all over the world have highlighted the environmental factors that affect the abundance and distribution of V. parahaemolyticus, such as water salinity, temperature, turbidity, and the levels of chlorophyll and organic matter in suspension (10). Although the mechanism underlying human infection by V. parahaemolyticus is not completely understood, there are two hemolysins that are commonly recognized as pathogenicity indicators: thermostable direct hemolysin (TDH), which is a pore-forming protein involved in bacterium invasion, and TDH-related hemolysin (TRH), which plays a significant role in virulence (10)(11)(12). Most of the clinical isolates of V. parahaemolyticus possess tdh and/or trh; however, a relatively low number of environmental isolates were found to carry these genes (10,13).…”
mentioning
confidence: 99%
“…Intriguingly, temperature was not significantly related to concentrations of pathogenic strains [32,39]. By contrast, Jones et al [36] observed that when temperature did not affect total concentrations of V. parahaemolyticus, it did have an effect on tdh-and trh-positive strains.…”
Section: Introductionmentioning
confidence: 94%
“…For V. vulnificus, most studies find that temperature drives bacterial concentrations [25][26][27][28][29][30][31][32][33][34], V. vulnificus most easily being isolated in oyster tissues with a temperature range from 158C to 178C [26,27,29,32]. Exceptions include Parvathi et al [35], Jones et al [36] and Givens et al [37], though a common limitation to these studies is a lack of variation in temperature over the sampling period. Models assume that salinity does not play a factor in V. vulnificus abundance, but reported effect of salinity on V. vulnificus varies from location to location, including insignificant [25,30,32,37], positive [29], inhibitory [26,28,31,38] or nonlinear [27] associations.…”
Section: Introductionmentioning
confidence: 99%